The importance of providing palliative care for patients with severe COVID-19 in Indonesia - Effendy, Christantie; Kristanti, Martina Sinta (Belitung Nursing Journal, 2021)
Patients with Coronavirus Disease 2019 (COVID-19), particularly those with a severe condition, might not survive. Pandemic situation challenges the healthcare providers in addressing palliative care to the patients. This paper aimed to describe the importance of providing palliative care for patients with severe COVID-19 in Indonesia. We used a case scenario to illustrate the common condition experienced by a patient with severe COVID-19. Health care providers in Indonesia could address palliative care for patients with COVID-19 by focusing on controlling the symptoms, avoiding futile intervention, and connecting the patients and their families. Nurses need to consider the patients’ needs for family supports, even though not in physical or psychosocial support, and help the patients who need end-of-life care to be dying with dignity. Communication technology must be utilized optimally by healthcare providers to realize the communication among the patients, families, and health workers.